Lake level reconstruction of Huangqihai Lake in northern China since MIS 3 based on pulsed optically stimulated luminescence dating. (April 2016) - Zhang, Jingran; Tsukamoto, Sumiko; Jia, Yulian; Frechen, Manfred
ABSTRACT: Lake sediments provide rich information about past climatic variations in the drainage area. Five outcrops from Huangqihai Lake in northern China were investigated to reconstruct the lake level fluctuations during the late Pleistocene and Holocene. A chronological framework ranging from ∼34 to ∼8 ka was established by pulsed optically stimulated luminescence dating using sand‐sized quartz and by radiocarbon dating techniques. The chronological and geological evidence demonstrates that the lake level of Huangqihai reached a peak elevation of ∼1340 m [>77 m above the present lake level (a.p.l.l)] during the early Holocene. Such highstand was sustained from ∼10 to ∼8 ka and retreated towards the middle and late Holocene. Between ∼50 and ∼11 ka, aeolian and fluvial deposition prevailed around the lake basin and no lake sediment was found above 1277 m (∼14 m a.p.l.l.), demonstrating a low lake level during this interval compared with that of the early Holocene.